Transhumanisme dalam Perspektif Teologi Islam: Rekonstruksi Konsep Kemanusiaan di Era Digital - Rika Amelia Nasution; Rudi Yuyung; Nursyahira Putri; Rahmat Fauzi (Yayasan Albahriah Jamiah Indonesia, 2025)
The development of transhumanism in the digital era presents a new paradigm of humankind that emphasizes the enhancement of biological, cognitive, and existential capabilities through artificial intelligence, biotechnology, and genetic engineering. This idea poses a serious challenge to the traditional concept of humanity, especially in the context of Islamic theology, which positions humans as beings with souls, morals, and responsibilities before God. This study aims to analyze transhumanism from an Islamic theological perspective and reconstruct the concept of humanity based on the principles of monotheism, caliphate, and the human spirit. Using qualitative methods through a textual-theological analysis approach, this study interprets classical texts (turāṡ) and contemporary discourses to formulate a conceptual synthesis between Islamic theology and posthuman ideas. The results show that the epistemology of transhumanism is rooted in secular rationalism and liberal humanism, which interpret humans as autonomous entities capable of transcending their biological limitations, while Islamic theology asserts that true humanity originates from a spiritual dimension connected to God. Through theological reconstruction, transhumanism can be transformed into an ethical discourse aligned with the values ​​of monotheism and the responsibilities of the caliph, where technology serves as a means of improving spiritual and social quality, not as an attempt to eliminate human nature. This research ultimately formulates a transformative model of Islamic Humanitarian Theology in the digital era—combining spirituality, rationality, and the ethics of civilized technology use. Thus, Islamic theology offers an alternative paradigm to transhumanism by affirming humans as spiritual and moral beings who manage technology ethically and are oriented towards universal welfare.